Do gender differences matter in Acute Heart Failure? Insights from Indian College of Cardiology – National Heart Failure Registry, India - P.B. Jayagopal; C.N. Manjunath; A. Jabir; Sridhar L. Sastry; Veena Nanjappa; P.R. Vaidyanathan; Johny Joseph; Soma Sekhar Ghanta; P. Manokar; Nitin Kabra; Dharmendra Jain; Vinod Sharma; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Real-world investigations focused on gender-associated characteristics of Acute Heart failure (AHF) are lacking. The current study, from a national heart failure registry, aims to investigate gender-based patterns and outcomes among AHF patients in India. Methods: This prospective Indian College of Cardiology National Heart Failure Registry enrolled patients admitted with AHF in 17 centres from 2019 to 2021. Demographics, aetiology, co-morbidities, laboratory investigations, electrocardiogram, and echo parameters were captured. In-hospital 30-day and one-year mortality rates were recorded. The prescription and adherence to the three Guideline Directed Medical Therapy (GDMT) prescription in 2019–2021 were also captured at discharge. Mortality rate Gender-based comparisons were tested at a 5 % level of significance. Results: The study enrolled 5182 AHF patients, 66.7 % male (M) and 33.3 % female (F). The mean age of the male (M) population was 60.9 ± 13.3, and the female (F) population was 62.8 ± 14 years. Women had a higher prevalence of heart failure with preserved ejection fraction (HFpEF)(F:12.9 %, M:7.3 %;P < 0.0001), hypertension (F: 57.2 %, M: 52.4 %; P = 0.0011) and arrhythmia (F:15.2 %, M:11.7 %;P = 0.0005). Men had a higher incidence of ischemic heart disease (M:76.2 %, F:67.5 %; P < 0.001). Adherence to Renin-angiotensin-aldosterone system (RAAS) inhibitors, Beta-blockers and Mineralocorticoid receptor antagonists (MRAs) was low (18.8 % (M); 15.9 % (F)). The mortality rate, in-hospital mortality was 6.9 % (M:6.5 %, F:7.7 %), up to one-month was 11.8 % (M:11.6 %, F:12.3 %) or one-year was 18.1 % (M:17.8 %, F:18.6 %). Conclusion: Women represent one-third of the population with AHF. Hypertension and HFpEF were more common in women, while ischemic heart disease was more prevalent in men. No gender-based differences were observed in the mortality outcomes. Both groups had low GDMT adherence. This calls for effective strategies to improve HF care in the country.